Sosialisasi Pentingnya Kesehatan Mental Bagi Siswa di Era Digital - Meylia Sari; Dina Rizki Fadilla; Yolanda Bahar; Maula Salsabila; Meta Silvia; Fadila Rasti Ramadana (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2026)
The rapid development of digital technology has provided convenience in accessing information and communication. However, uncontrolled use of digital technology may negatively affect students' mental health, including stress, anxiety, decreased self-esteem, and social media addiction. This community service program aimed to increase students' understanding of the importance of maintaining mental health in the digital era. The methods included educational socialization, interactive lectures, discussions, and evaluation through pre-tests and post-tests. The program involved 50 secondary school students. The results indicated an increase in students' understanding of mental health concepts, the impact of digital media use on psychological well-being, and strategies to maintain mental health through social media management, stress management, and strengthening social relationships. Participants' average understanding increased from 62% in the pre-test to 89% in the post-test. This program successfully enhanced students' awareness of maintaining mental health to face challenges in the digital era